A new species of Philophylla Rondani (Diptera: Tephritidae: Trypetini) from New Caledonia, recognized based on female postabdominal structure and molecular sequence data - Han, Ho-Yeon; Norrbom, Allen L. (Zootaxa, 2008)
Philophylla millei, n. sp., from New Caledonia is described and its relationship analyzed. This species was recorded previously as Anastrephoides sp. based on a single female, which closely resembles the eastern Palaearctic species Anastrephoides matsumurai Shiraki. Whether this similarity reflects the close relationship of these species or a case of convergent evolution was examined using morphology and molecular data. We examined both male and female specimens of the New Caledonian trypetine species and sequenced the mitochondrial 16S ribosomal RNA gene of this species and related trypetine species. This new species is a member of the genus Philophylla Rondani based both on the female postabdominal structure as well as DNA sequence data.